The value relevance of purchased goodwill in Malaysian firms: the pre- and post-IFRS evidence - Al-Hiyari, Ahmad; Abdul Latif, Rohaida; Amran, Noor Afza (International Academy of Business and Economics (IABE), 2016)
Following the adoption of International Financial Reporting Standards (IFRS) in Malaysia, the accounting for goodwill has changed from systematic amortisation to a method based solely on periodic impairment testing.The objective of the impairment test is to ensure that reported goodwill does not have carrying amount in excess of its recoverable amount.Nevertheless, many critics suggest that the new method may allow managements to engage in opportunistic earnings manipulation activities.In this study, we examine the question of whether goodwill is more value relevant after adoption of an IFRS in Malaysia. Using panel data of non-financial firms listed on the Bursa Malaysia over the period from 2002 to 2010, we find evidence that goodwill is not value relevant in either the pre-and post IFRS periods. These findings are in line with the opponents of the new standards, who claim that, the use Fair Value Accounting (FVA) in the reporting of goodwill increases the opportunities for managerial opportunisms.Therefore, the consequences FVA devoid of relevant information for shareholders.We conclude that the existence of an unfavorable environments in Malaysia impedes efficient implementation of the new impairment regime.